2019
DOI: 10.21203/rs.2.16117/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the clinical outcomes of Scarf and Chevron Osteotomy for Hallux Valgus Deformity: a meta-analysis of randomized controlled trial

Abstract: Background Scarf and Chevron Osteotomy have been widely used for Hallux Valgus Deformity (HVD) to correcting hallux valgus angle (HVA) and intermetatarsal 1-2 angle (IMA), but there still have controversy which approach is the best way to repair HVD,this study aims to use meta-analysis to evaluate the clinical outcomes of Scarf and Chevron Osteotomy for Hallux Valgus Deformity.Methods Pubmed, Embase, Medline and Cochrane library databases were searched for relevant studies published before September 1, 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In the literature, it has been reported that the average amount of bleeding in total knee arthroplasty operations is between 800-1800 ml [4,5]. Blood transfusion applied due to bleeding prolongs both the reha-bilitation period and the length of hospital stay [6]. It also causes severe complications such as transfusion reaction, infection, metabolite imbalances, hemolysis, and immune system inhibition [7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it has been reported that the average amount of bleeding in total knee arthroplasty operations is between 800-1800 ml [4,5]. Blood transfusion applied due to bleeding prolongs both the reha-bilitation period and the length of hospital stay [6]. It also causes severe complications such as transfusion reaction, infection, metabolite imbalances, hemolysis, and immune system inhibition [7][8][9].…”
mentioning
confidence: 99%
“…Tranexamic acid can be administered in a number of different ways (oral, intravenous, intra-articular). Although there are studies showing that each method is effective in reducing bleeding, which method and which dose are most effective in patients with total knee arthroplasty remain controversial [1,6].…”
mentioning
confidence: 99%